1976
DOI: 10.1007/bf02532865
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic principles ofCicer Arietinum: Biochanin‐A and formononetin

Abstract: Two isoflavones, biochanin-A and formononetin isolated from gram Cicer arietinum, have been shown to possess hypolipidemic properties for Triton WR-1339 induced hyperlipidemia in male albino rats, when administered as a crude extract or as individual compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Biochanin A (5, 7-Dihydrox-4’-methoxyisoflavone, abbreviated as BCA) is the main effective component of Trifolium pratense L. , which has estrogen-like characteristics and is mainly used in the treatment of menopausal syndrome in women 10 , 11 . It has been revealed that BCA has a variety of pharmacological effects, such as anti-tumor, anti-inflammatory, anti-osteoporosis, antibacterial, hypolipidemic, etc 12 16 . Previous studies have proved that BCA can inhibit inflammatory responses in a variety of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Biochanin A (5, 7-Dihydrox-4’-methoxyisoflavone, abbreviated as BCA) is the main effective component of Trifolium pratense L. , which has estrogen-like characteristics and is mainly used in the treatment of menopausal syndrome in women 10 , 11 . It has been revealed that BCA has a variety of pharmacological effects, such as anti-tumor, anti-inflammatory, anti-osteoporosis, antibacterial, hypolipidemic, etc 12 16 . Previous studies have proved that BCA can inhibit inflammatory responses in a variety of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in the fracture-repair process, as evidenced by its role in enhancing bone regeneration in a mouse model of cortical bone defect [9]. Moreover, it has hypolipidemic properties and free radical scavenging activity that prevent the formation of lipid peroxidation [10, 11]. FMNT is also reported to have a neuroprotective effect against oxidative stress and excitotoxicity instigated by hydrogen peroxide and L-glutamate [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Further, several research works have demonstrated the cholesterol lowering effects of C. arientum in different types of hyperlipidemias such as induced by diet[ 24 25 26 ] or triton. [ 27 ] The sprout extracts of chickpea were able to prevent estrogen deficiency induced bone loss. [ 23 ] However, the antihyperlipidemic effect of C. arientum was not studied in estrogen deficiency-induced hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%